Digital Leadership Transformation and Spiritual Well-being as HRM Strategies to Improve Sustainable MSME Performance - Maulana Maulana; Nopa Dwi Saputra; Eko Triawan; Muhammad Rasyid Ridho (Relasi : Jurnal Ekonomi, 2026)
This study aims to analyze the role of digital leadership transformation and spiritual well-being as part of a human resources management (HRM) strategy in improving the performance of sustainable MSMEs in Lubuklinggau City. In the digital era and economic uncertainty, MSMEs are required to adapt not only technologically but also personally and organizationally. This study uses a quantitative approach with the AMOS-based Structural Equation Modeling (SEM) method, and involves 100 respondents who are MSME owners/managers spread across Lubuklinggau City as samples. The variables studied include spiritual well-being, interpersonal communication, digital leadership, and sustainable performance of MSMEs. The results of the study indicate that digital leadership and spiritual well-being have a significant positive effect on sustainable MSME performance, both directly and through interpersonal communication mediation. This finding confirms that an HRM strategy that integrates spiritual values, technology-based leadership, and effective communication can encourage the resilience and sustainability of MSMEs in facing global challenges. The implications of this study contribute to the development of a value-based and technology-based HR management model that is relevant to the context of MSMEs in developing areas.